Thinking (and Moving) Beyond Walls And Cages: Bridging Immigrant Justice and Anti-Prison Organizing In the United States - Loyd, Jenna M. (Social justice, 2009)
This article suggests a relation between immigration justice and anti-prison advocacy in the United States. The authors describe prisons as a sort of border as a means of making a comparison to efforts to intensify U.S. border fortification. The article cites examples of policing practices that are stated to isolate groups both discursively and politically from each other. The article discusses how criminalization and exclusionary migration policies create categories of people who are not given the same rights as U.S. citizens.